Integrating technology and localization: A new path for smart tourism in the Mekong Delta, Vietnam - Diem, Nguyen Thuy; Pham, Hang Thu (Edelweiss Applied Science and Technology, 2025)
This study analyzes the potential and challenges of Smart Cultural Tourism in the Mekong Delta, a region renowned for its rich cultural heritage yet increasingly pressured by globalization and climate change. Utilizing a mixed-methods approach—combining qualitative analyses (SWOT analysis, semi-structured interviews) and quantitative data (field surveys)—the research comprehensively examines how key cultural elements, particularly amateur music (a UNESCO-recognized intangible heritage), can be integrated into innovative digital tourism strategies. The findings indicate that each province (Can Tho, Tra Vinh, Tien Giang, and Vinh Long) possesses unique strengths, including technological infrastructure, Khmer cultural heritage, culinary–ecological diversity, and homestay-based community tourism. Incorporating Đờn ca tài tử into both traditional and digital forms (livestreaming, VR/AR) creates hybrid spaces where cultural memory and technological innovation converge. The study underscores that Smart Cultural Tourism is not merely a technological transition but a crucial opportunity to revitalize community memory and foster regional–international connectivity. In practical terms, these results provide a scientific and empirical basis for local authorities to formulate smart, sustainable tourism policies, enhance promotional capabilities, train digitally skilled human resources, develop culturally rooted tourism products, and expand ASEAN–international cooperation.